Blockchain - Laurence, Tiana (New Delhi Wiley, 2017)
Find out what Blockchain is, how it works, and what it can do for you Blockchain is the technology behind Bitcoin, the revolutionary 'virtual currency' that's changing the way people do business. While Bitcoin has enjoyed some well-deserved hype, Blockchain may be Bitcoin's most vital legacy. This is the ideal starting place for business pros looking to gain a better understanding of what Blockchain is, how it can improve the integrity of their data, and how it can work to fundamentally change their business and enhance their data security.
Getting started with blockchain. Introducing blockchain ; Picking a blockchain ; Getting your hands on blockchain -- Developing your knowledge. Beholding the bitcoin blockchain ; Encountering the ethereum blockchain ; Regarding the ripple blockchain ; Finding the factom blockchain ; Digging into digibyte -- Powerful blockchain platforms. Getting your hands on hyperledger ; Applying Microsoft azure ; Getting busy on IBM bluemix -- Industry impacts. Financial technology ; Real estate ; Insurance ; Government ; Other industries -- The part of tens. Ten free blockchain resources ; The ten rules to never break on the blockchain ; Ten top blockchain projects.
Includes index.
Keywords: Blockchains (Databases); Electronic funds transfers; Bitcoin; Data encryption (Computer science); Electronic commerce; Netzwerk; Computersicherheit